Analisis Dampak Perilaku Konsumtif Remaja: Perspektif Riba Dalam Penggunaan PayLater di Platform E-Commerce Shopee - Nayla Izzatul Laili; Madian Muhammad Muchlis (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
Discounts and promotions are the main motivation, while most feel that the financial risks outweigh the benefits. This research aims to highlight aspects of financial risk associated with adolescent consumption choices in the e-commerce era so that this study contains an analysis of the impact of using the "PayLater" option on Shopee on adolescent consumption behavior, focusing on financial implications and usury perspectives. The method used in this study was qualitative and literature with research subjects of adolescents aged 17-21 years. The results of this study show that the use of the "PayLater" option on Shopee affects teenagers' consumption behavior in a complex way. The majority of teenagers have a neutral point of view influenced by friends and Shopee promotions.